Optimization Design of Honorarium for Posyandu Cadres in Gunungkidul Regency - Wafumilena, Erny Riana; Nurhasanah, Fauziah; Awuni, Nur Syamsiah; Hafizah, Nurul (BKM Public Health and Community Medicine, 2024)
Purpose: The highest prevalence of stunting in the Special Region of Yogyakarta, according to SKI 2023, is found in Gunungkidul Regency, with a rate of 22.2%. According to BPS data, poverty is a significant contributing factor, with the poverty rate in Gunungkidul reaching 17.69% in 2022. This situation demands urgent attention from the Gunungkidul government, particularly in achieving the national target of reducing stunting rates amid high poverty levels. Posyandu (Integrated Health Post) cadres, as extensions of Puskesmas (Community Health Centers), play a critical role in this effort, making their welfare essential. The lack of specific guidelines on honorarium challenges maintaining and motivating Posyandu cadres. Current policies are not detailed or specific regarding the honorarium for Posyandu cadres, and the amounts vary across different villages due to the absence of a standardized policy from the Gunungkidul government. Methods: This quantitative study used a cross-sectional design and secondary data analysis. Data were collected from national surveys conducted in March 2023. Statistical analysis included frequency distribution, chi-square tests, and logistic regression to identify relationships between variables. Results: Health insurance ownership was not significantly associated with increased utilization of outpatient health services compared to those without insurance (OR 1.04, 95% CI 0.93-1.1). However, insurance ownership was linked to a lower likelihood of catastrophic health expenditures at all thresholds: 10% of total expenditure (OR 0.69, 95% CI 0.58-0.82), 25% of total expenditure (OR 0.47, 95% CI 0.37-0.59), and 40% of non-food household expenditure (OR 0.55, 95% CI 0.44-0.68). Other variables influencing catastrophic health expenditures included age, education, occupation, economic level, health complaints, and activity limitations. Conclusion: Establishing a standardized honorarium policy for Posyandu cadres in Gunungkidul Regency can improve performance and service delivery by Posyandu cadres in each village. This initiative is expected to significantly contribute to achieving regional health program targets and addressing stunting.